Colossal : Kunst - Fakt - Fiktion. - Pantazou, Christina; Tauss, Susanne (Osnabrück : Landschaftsverband Osnabrücker Land e.V., 2009)
Cabrita Reis, Pedro ; Delvoye, Wim ; Lange, Anna ; Lemmen, Hans ; Maes, Ives ; Sánchez Castillo, Fernando ; Tunn, Susanne ; Slominski, Andreas ; Bartolini, Massimo ; Chafes, Rui ; Nakovska, Slava ; Brock, Bazon ; Hagebölling, Wilfried ; Bonvicini, Monica ; Gygi, Fabrice ; Oppenheim, Dennis ; Minjun, Yue ; Rose, Anette ; Bock, Katinka ; Brummack, Heinrich
Colossal. Kunst - Fakt - Fiktion, 2000 Jahre Varusschlacht, 25. April 2009 - 31 Dezember 2011
boek